ELASTO-PLASTIC ANALYSIS FOR DISPLACEMENTS OF GRANULAR PILE ANCHORS (GPA) IN NON-HOMOGENOUS GROUND - B. Vidyaranya; M. R. Madhav; M. Kumar (International Association of Lowland Technology, 2009)
Granular piles improve the behavior of the soil by increasing bearing capacity, accelerate consolidation, reduce settlements, and mitigate liquefaction related damages by reinforcement and densification effects. Granular piles can be made to resist pullout or uplift forces by placing an anchor at the base and attaching the same by a cable or rod to the footing to transfer the applied pullout forces to the bottom of the GP termed Granular Pile Anchor (GPA). The elasto-plastic response of GPA in non-homogenous ground is presented considering the shear stress at the interface to be limited to the undrained strength of the soil.